Depth of response and response kinetics of isatuximab plus carfilzomib and dexamethasone in relapsed multiple myeloma - Martin, Thomas; Mikhael, Joseph; Hajek, Roman; Kim, Kihyun; Suzuki, Kenshi; Hulin, Cyrille; Garg, Mamta; Quach, Hang; Sia, Hanlon; George, Anup; Konstantinova, Tatiana; Risse, Marie-Laure; et al. (Blood advances, 2022)
The IKEMA study (Randomized, Open Label, Multicenter Study Assessing the Clinical Benefit of Isatuximab Combined With Carfilzomib [Kyprolis®] and Dexamethasone Versus Carfilzomib With Dexamethasone in Patients With Relapse and/or Refractory Multiple Myeloma Previously Treated With 1 to 3 Prior Lines; #NCT03275285) was a randomized, open-label, multicenter phase 3 study investigating isatuximab plus carfilzomib and dexamethasone (Isa-Kd) vs Kd in patients with relapsed multiple myeloma. This subanalysis analyzed the depth of response of Isa-Kd vs Kd. The primary end point was progression-free survival (PFS); secondary end points included overall response rate, very good partial response or better (≥VGPR) rate, complete response (CR) rate, and minimal residual disease (MRD) negativity rate (assessed in patients with ≥VGPR by next-generation sequencing at a 10-5 sensitivity level). At a median follow-up of 20.7 months, deeper responses were observed in the Isa-Kd arm vs the Kd arm, with ≥VGPR 72.6% vs 56.1% and CR of 39.7% vs 27.6%, respectively. MRD negativity occurred in 53 (29.6%) of 179 patients in the Isa-Kd arm vs 16 (13.0%) of 123 patients in the Kd arm, with 20.1% (Isa-Kd, 36 of 179 patients) vs 10.6% (Kd, 13 of 123 patients) reaching MRD-negative CR status. Achieving MRD negativity resulted in better PFS in both arms. A positive PFS treatment effect was seen with Isa-Kd in both MRD-negative patients (hazard ratio, 0.578; 95% CI, 0.052-6.405) and MRD-positive patients (hazard ratio, 0.670; 95% CI, 0.452-0.993). Exploratory analysis indicates that both current CR and MRD-negative CR rates are underestimated due to M-protein interference (potential adjusted CR rate, 45.8%; potential adjusted MRD-negative CR rate, 24.0%). In conclusion, there was a clinically meaningful improvement in depth of response with Isa-Kd. The CR rate in Isa-Kd was 39.7%. Mass spectrometry suggests that the potential adjusted CR rate could reach an unprecedented 45.8% of patients treated with Isa-Kd.
Keywords: Neoplasm Recurrence, Local; Oligopeptides; Neoplasm, Residual; humanizované monoklonální protilátky; lidé; Multiple Myeloma; Antibodies, Monoclonal, Humanized; oligopeptidy; mnohočetný myelom; reziduální nádor; dexamethason; Dexamethasone; lokální recidiva nádoru; Humans